(untitled) - Marshak, Stephen (New York, 2005)
This survey is the first to weave together the three major intellectual revolutions in the Earth Sciences that have occurred in the last forty years -- the theory of plate tectonics, the Earth-Systems-Science synthesis, and the connection between the evolution of life and the evolution of the Earth itself.
Keywords: Geology; Textbooks